Direito fundamental à educação e o impacto orçamentário na adequação da escola pernambucana aos imigrantes não lusófonos: um recorte para os imigrantes venezuelanos. - Silva, Renata Esteves Seabra e (2023)
The present dissertation aims to point out the barriers to fundamental education in terms of language leveling among native and foreign citizens. Consequently, identify material resources that facilitate such leveling and, therefore, whether their cost at the expense of the state of Pernambuco is feasible. The research focuses on what is recommended by the Education Guidelines and Bases Law, the Constitution of the Federative Republic of Brazil, the Migration Law, the Refuge Law and the Child and Adolescent Statute in order to ascertain the limits between what says the norm and what must be done in order to bring the foreign citizen closer to the education provided to the native citizen. In this sense, it goes through the analysis of the adequacy or not of the public policies carried out by the state of Pernambuco in the reception of this Spanish-speaking immigrant. The research starts from the hypothesis that language and ethnic grouping can give rise to a new design of the local community promoting an apartheid policy. Circumstance that affirms the immigrant as a threat, as an element carrying danger, thus creating a barrier to the process of social transformation in which the different States live. Finally, it is understood that through the proposed research it will be possible to carry out a scientific diagnosis of the educational level proposed by the state of Pernambuco to migrants and perhaps present a set of proposals that will support the development of an adequate public policy for the insertion of this immigrant. In this sense, the study was based basically on the use of bibliographical procedures, mixed qualitative-quantitative approach, exploratory objective, theoretical methods, due to which possible criticisms of normative and doctrinal texts related to the theme were observed and analyzed. Circumstance that makes it possible to affirm the methodology based on the investigation through logical thinking, analysis of the critical observation of the contents that aim to measure the economic impact of the arrival of Venezuelans in Brazil with regard to the attendance of their educational formation.